2018
DOI: 10.1007/s00167-018-5248-0
|View full text |Cite
|
Sign up to set email alerts
|

Promising early outcomes of a novel anatomic knee system

Abstract: Purpose The primary aim of this study was to report the early clinical and radiographic outcomes of patients who have been treated with total knee arthroplasty (TKA) using the Persona knee system. The secondary aim was to compare patient‐reported outcomes (PROs) of the Persona knee system to those of the NexGen implant. Methods A registry‐based study of a consecutive series of 112 patients (129 knees) treated with the Persona knee system from a single center was conducted. Preoperative, 1‐year, and 2‐year radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…A novel total knee system, introduced to the European market in 2012, was developed to improve the mechanics of the knee replacement by making a more anatomically accurate knee implant [ 1 , 2 ]. A new highly crosslinked ultrahigh-molecular-weight polyethylene (UHMWPE) formulation incorporating the antioxidant vitamin-E (alpha-tocopherol) aims to reduce oxidation and maintain wear resistance and strength throughout the life of the implant [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel total knee system, introduced to the European market in 2012, was developed to improve the mechanics of the knee replacement by making a more anatomically accurate knee implant [ 1 , 2 ]. A new highly crosslinked ultrahigh-molecular-weight polyethylene (UHMWPE) formulation incorporating the antioxidant vitamin-E (alpha-tocopherol) aims to reduce oxidation and maintain wear resistance and strength throughout the life of the implant [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various kinematic and biomechanical studies have demonstrated the design benefits of the novel anatomic knee system [ 7 – 10 ]. In addition, data from registries and clinical studies show excellent survivorship and clinical outcomes at 1 to 3 years [ 1 , 11 ]. The predecessor to the novel anatomic knee design represents a successful and proven implant for TKA with scientific evidence for its remarkable clinical long-term outcome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated differences between cruciate retaining PERSONA and NexGen implants, but this is the first to evaluate the difference between these two posterior stabilized implants [27][28][29]. There is still a lack of studies, especially randomized-controlled studies comparing the outcome of PERSONA PS design to that of NexGen LPS.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, adequate time for evaluation and surveillance should be defined based on the specific implant's function and the disease process treated. 27 For example, short-term outcomes of a new syndesmotic device are valuable because osseous and ligamentous healing typically occur within several months after ankle fracture. Arbitrary requirements for lengthy follow-up (regardless of disease process) could result in initial widespread use of unsafe or ineffective implants before the literature and/or regulatory bodies drive a change in practice.…”
Section: Discussionmentioning
confidence: 99%